1987
DOI: 10.1002/anie.198701701
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and Charged Biradicals, Zwitterions, Funnels in S1, and Proton Translocation: Their Role in Photochemistry, Photophysics, and Vision

Abstract: A knowledge of the geometries at which excited molecules return to the electronic ground state (So) is essential for the understanding of the structures of photoproducts. Particularly good candidates are geometries corresponding to local minima on the S, (lowest excited singlet) and TI (lowest triplet) surfaces, as well as So-Sl conical intersections (funnels). Given sufficient effort, such geometries can nowadays be found numerically for small enough molecules. Still, it is interesting to ask whether more app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
333
2
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(352 citation statements)
references
References 81 publications
(11 reference statements)
14
333
2
3
Order By: Relevance
“…[40][41][42][43][44][45][46][47][48][49][50][51][52] Wave function theories restricted to a single determinant are poorly suited to the description of such species since singlet biradicals are intrinsically two determinantal. 53,54 Moreover, even when oxidation states more likely to be characterized as closed shell in nature are considered, e.g., ͓LCu͑III͔͒ 2 ͓O͑2−͔͒ 2 , computational studies have found that large contributions from dynamical correlation effects influence relative isomer energetics. [40][41][42][47][48][49]51,52 In this section, we apply the RASPT2 method to two problems previously studied in considerable detail using a wide range of theoretical models ͑see Fig.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48][49][50][51][52] Wave function theories restricted to a single determinant are poorly suited to the description of such species since singlet biradicals are intrinsically two determinantal. 53,54 Moreover, even when oxidation states more likely to be characterized as closed shell in nature are considered, e.g., ͓LCu͑III͔͒ 2 ͓O͑2−͔͒ 2 , computational studies have found that large contributions from dynamical correlation effects influence relative isomer energetics. [40][41][42][47][48][49]51,52 In this section, we apply the RASPT2 method to two problems previously studied in considerable detail using a wide range of theoretical models ͑see Fig.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…1,13 Some chemists prefer the name "biradical", 14 but others call molecules with two positive charges "dications" and molecules with two negative charges "dianions". Therefore, calling molecules that, at least potentially, have two unpaired electrons "diradicals" has the virtue of a consistency.…”
Section: Wave Functions For Diradicals and The Qualitative Predictionmentioning
confidence: 99%
“…64 In the limit where |B is completely dominated by the subspace spanned by |lb 2 r and |l 2 r 2 , the one-electron density matrix would be a multiple of the identity in the subpace spanned by the left and right orbitals l and r. This is the defining characteristic of a biradical. 69 This suggests that it is inappropriate to think of the singlet pairing in state |B as indicative of a "long bond." This is consistent with the conclusions of an analysis of the valence-bond electronic structure of allyl ions.…”
Section: B Diabatic Statesmentioning
confidence: 99%